Developing a conceptual framework for patient safety culture in emergency department: A review of the literature. (5th September 2018) - Alshyyab, Muhammad Ahmed; FitzGerald, Gerard; Dingle, Kaeleen; Ting, Joseph; Bowman, Paula; Kinnear, Frances B.; Borkoles, Erika
Summary: Patient safety culture is a critical component of modern health care. However, the high‐paced, unpredictable nature of the emergency department (ED) environment may impact adversely on it. The aim of this paper is to explore the concept of patient safety culture as it may apply to emergency health care, and to propose a conceptual framework that could form the basis for interventions designed to improve it. This is a systematic review of the literature. A search was undertaken of common electronic bibliographic databases using key words such as safety culture, safety climate, and Emergency Department . Articles were analysed for consistent themes with the aim to construct a conceptual framework. Ten articles met the inclusion criteria that specifically examined safety culture in the ED. Synthesis of the literature resulted in the emergence of three overarching themes of ED practice found to impact on safety culture in the ED. These were the dimensions of patient safety culture, the factors influencing it, and the interventions for improving it. A conceptual framework was constructed that identifies elements that significantly impact the patient safety culture in the ED. This framework may assist managers and researchers to take a comprehensive approach to build an effective safety culture in ED setting.